Paul's Rhetorical Efforts to Establish Good Will in First Thessalonians. (June 2022) - Berglund, Carl Johan
Ancient oratory ordinarily begins with an effort of captatio benevolentiae – the rhetorical strategy of praising and lauding the audience to make them well-disposed toward the speaker, attentive and receptive to your message – especially before controversial claims or challenging demands. In First Thessalonians, such efforts are manifest not only in the introduction in ch. 1, but throughout the narration in chs. 2–3, which implies that the senders are preparing for a particularly sensitive topic. The first exhortation to appear after these efforts cease, the exhortation to sexual holiness in 1 Thess. 4.3-8, must therefore represent the primary purpose of the letter. The euphemistic language used in this request makes it difficult to understand what kind of πορνεία ('sexual immorality') Paul, Silvanus and Timothy are arguing against, but the most likely interpretation is that they want the Thessalonian Christians to stop using their slaves and former slaves for sexual purposes.